PARTNER project post-documentation study. Condition assessment of field exposure site cubes. Results of microstructural analyses. (December 2022) - Fernandes, Isabel; Leemann, Andreas; Fournier, Benoit; Menendez, Esperanza; Lindgård, Jan; Borchers, Ingmar; Custódio, João
Abstract: Within the PARTNER project (2002–2006) concrete cubes were exposed for 13 years at different exposure sites in Europe. Subsequently, cores were extracted from these cubes for further investigation within the framework of RILEM TC 258-AAA. The aim of the microstructural study is to relate the microstructural features to cube expansion and to investigate a possible relation between aggregate type and chemical composition of ASR product. Both the Damage Rating Index (DRI) determined on polished sections and the Qualitative Damage Assessment (QDA) performed on thin sections show a relation to cube expansion. However, damage characteristics depend on the texture and composition of the aggregates, affecting the results of both used methods. The composition of ASR products formed in aggregate particles varies in a very small range showing no systematic influence of aggregate type or exposure site.